THE IMPLEMENTATION OF INDONESIA’S COUNTER PIRACY STRATEGIES THROUGH MULTILATERAL COOPERATION IN THE MALACCA STRAIT (2004-2009) - Bustanul Arifin; Nur Afni Damanik (Universitas Pelita Harapan, 2020)
International Maritime Organization data shows that the trend in piracy in the Malacca Strait was significant from 2000-2004. In 2005, the Malacca Strait was categorised as a high-risk zone by the Lloyd’s Joint War Risk Committee. In the 2000s, post 9/11 terrorist attacks have galvanised the rising concern of the international community over the security of the Malacca Strait since there was a concern that sea piracy could lead to sea terrorism. Prior to 2004, apart from conducting unilateral patrols, Indonesia had bound itself to engage in bilateral cooperation with Malaysia and Singapore respectively. During 2004-2009, there were multiple multilateral cooperation initiatives proposed to Indonesia of which Indonesia responded in different ways. This research employs the qualitative method utilising journals, reports, official documents, and books to analyse the implementation of Indonesia’s counter piracy strategy in the Strait of Malacca from 2004-2009. Indonesia’s counter piracy strategy was implemented through MALSINDO Coordinated Patrol, Eyes in the Sky, which is later followed by the Malacca Strait Patrol – Intelligence Exchange Group (MSP-IEG). The launch of coordinated sea patrols of MALSINDO in 2004 was followed with the air patrol of the Eyes in the Sky in 2005 and ended with the information sharing system through MSP-IEG in 2006. The multilateral cooperation conducted by Indonesia, Malaysia, and Singapore has shown a positive result regarding the strategy to counter piracy in the Malaca Strait.Bahasa Indonesia Abstract: Data Organisasi Kelautan Internasional menunjukkan tren perompakan di Selat Malaka dengan keberadaan yang signifikan dari 2000-2004. Pada tahun 2005, Selat Malaka dikategorikan sebagai zona berisiko tinggi oleh Komite Risiko Perang Bersama Lloyd. Pada tahun 2000-an, pasca serangan teroris 11 September telah membangkitkan keprihatinan masyarakat internasional atas keamanan Selat Malaka karena ada gagasan perompakan laut dapat beresiko terhadap terorisme laut. Sebelum tahun 2004, selain melakukan patroli sepihak, Indonesia telah mengikat diri untuk terlibat dalam kerjasama bilateral dengan Malaysia dan Singapura. Dalam periode 2004-2009, ada beberapa inisiatif kerjasama multilateral yang diajukan untuk penanggulangan perompakan di Selat Malaka dimana Indonesia memberikan respon yang berbeda. Penelitian ini menggunakan metode kualitatif berdasarkan jurnal, laporan, dokumen resmi, dan buku untuk menganalisa pelaksanaan strategi Indonesia dalam penanggulangan perompakan di Selat Malaka dalam periode 2004-2009. Strategi penanggulangan perompakan Indonesia diimplementasikan melalui Patroli Terkoordinasi MALSINDO, Eyes in the Sky, yang kemudian diikuti dengan Patrol Selat Malaka - Pertukaran Informasi Intelijen. Peluncuran patroli laut terkoordinasi MALSINDO pada tahun 2004 diikuti dengan patroli udara Eyes in the Sky pada tahun 2005 dan dilengkapi dengan sistem pembagian informasi melalui MSP-IEG pada tahun 2006. Kerjasama multilateral yang dilakukan oleh Indonesia, Malaysia, dan Singapura menunjukkan hasil positif terhadap strategi untuk menanggulangi perompakan di Selat Malaka.